How do you solve x + y =1 and 2x-y=-2 using substitution?

1 Answer
Jul 10, 2016

By eliminating x in the expression x+y=1, we get

x = 1-y, which we can plug in the second expression:

2(1-y)-y=-2

2-2y-y=-2

2-3y=-2

-3y+2=-2

-3y=-4

y=4/3

Knowing y, we can now find x by plugging the y-value into any of the above equations. For example, by plugging y=4 into the first equation, x+y=1, we get

x+4/3=1

x=-1/3

Explanation:

We can check whether these values satisfy the equations by plugging them back in:

First: x+y=1

-1/3 + 4/3 = 1 -> 4/3-1/3 = 1 -> (12-3)/(9) = 1 -> 9/9 = 1

Second: 2x-y=-2

2(-1/3)-4/3=-2 -> -2/3-4/3 = -2 -> -18/9 = -2